Genetic variability and differentiation in cultured white shrimp Penaeus (Litopenaeus) vannamei with low and high growth - M Rivera-García; JM Grijalva-Chon (Ciencias Marinas, 2005)
To find a relationship between allozyme heterozygosity and body size in cultured white shrimp, Penaeus (Litopenaeus) vannamei, a sample was taken at the end of an experimental culture; 72 small organisms of 7.1 ± 1.35 g average weights, and 72 large organisms of 17.5 ± 1.34 g average weights. Ten enzymatic systems were analyzed. Eighteen loci showed good resolution for genetic interpretation. Only EST-2*, EST-3*, EST-4*, EST-5*, and PGM* were polymorphic. Variability values (mean observed heterozygosity, mean number of alleles per locus, and polymorphism) for small shrimp were 0.029 ± 0.020, 1.5 ± 0.20, and 22%, whereas for large shrimp were 0.020 ± 0.010, 1.7 ± 0.20, and 28%. No significant difference was found in heterozygosity for both size-classes. All loci were out of Hardy-Weinberg equilibrium because of a heterozygote deficiency and high inbreeding values. EST-2* and PGM* showed differences in allelic frequencies among both size-classes, and an Fst value of 1.6% was recorded. Both size-classes have a different genetic population structure. Because of the poor information of the analyzed loci and to corroborate that EST-2* and PGM* are involved in growth, it would be necessary to follow the inheritance of those loci in successive generations.